The impacts of natural disasters on smallholder agriculture in rural Cameroon - Roland Azibo Balgah; Gertrud Buchenrieder (American Journal of Experimental Agriculture, 2014)
Problem: That climate change and subsequent natural disasters resulting from it will affect the agricultural sector is not new to anyone familiar with the disaster literature. However, the exact magnitude of such impacts remains to be estimated. Methodology: Using empirical evidence based on a 25 year old natural disaster in rural Cameroon, we attempt to provide estimates on the immediate and long term impacts of a natural disaster on smallholder agriculture. A standardized questionnaire is applied on 301 smallholder farming households to assess the short and long term impacts of the 1986 Lake Nyos disaster on agriculture, mainly eliciting responses through a recall process. This is complemented by participatory discussions and observations. Results: The results reveal that the disaster had significantly high negative impacts on livestock and human capital (P=0.01 respectively). Sampled households were found not have currently recovered even up to the levels before the 1986 disaster, after a quarter of a century. Conclusions: The implications of such disasters on the agricultural sector and their possible effects in the short and long term include increasing efforts towards prevention, and the use of data as basis for disaster management.
Keywords: 630; natural disaster; impact; smallholder agriculture; rural Cameroon